FAKTOR-FAKTOR YANG MEMPENGARUHI PENGETAHUAN IBU MENYUSUI TENTANG CARA MENINGKATKAN PRODUKSI ASI - Gustina, Irwanti; Rizmayandha, Dessy; Anggraeni, Legina (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Mother's Knowledge of How to Increase Breast Milk Production is a mother's effort to increase milk production in order to be able to provide exclusive breastfeeding to her baby until the age of 6 months without intake of other foods or drinks. If a baby is not given breast milk and is replaced with other fluids / foods other than breast milk, the baby will not get immunity, and will be malnourished. In the absence of antibodies, the baby will be susceptible to various diseases and increase infant mortality. So that the knowledge of parents greatly affects the increase in breast milk production. The aim of this study is to determine the factors that affect the knowledge of breastfeeding mothers about how to increase breast milk production in the kramat teak sub-district health center, East Jakarta. Sampling using accidental sampling. The research instrument used a questionnaire. This research method uses umivariate analysis. The results of the study there is a significant or significant relationship between education and information owned by mothers, but there are two variables that have no significant or significant relationship, namely parity and family support.The importance of providing education or information on how to increase milk production.